Program Perlindungan Bullying pada Anak Berkebutuhan Khusus di Sekolah Inklusi - Rahmawati, Hamidah Amni (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2019)
Special needs children in Indonesia did not have a bullying protection program in school. They need it to optimize their social and personal skill. Child protection had e wider scope, this research focused on special needs children's protection against bullying. Australia’s Child protection program was adopted and developed by researchers because it is appropriate to Indonesia’s culture. This research aimed to develop a bullying protection program for special needs children in inclusive schools and to know the expediency result of developing a bullying protection program for special needs children. This research was Research and Development (R&D) with Thiagarajan, Semmel, and Semmel model (1974). The phase of the Thiagarajan model was: (1) Define, (2) Design, and (3) Develop. The conclusion of the research is the development of a bullying protection program for special needs children it concluded that: (1) Developing of bullying protection program for special needs children in inclusive schools from the validation result model showed a score of 74.29%, (2) From the result of limited experiment calculation showed score 43.42%, it means that bullying protection program for special need children was suitably used. Keywords: protection, program, bullying.